A new species of Scinax (Anura: Hylidae) from the Ecuadorian Amazon - Travez Molina, Jorge Sebastian (2023)
We describe a new species of frog of the genus Scinax (Hylidae) from the Ecuadorian Amazon, provincia de Orellana. The new species is the sister species of Scinax chiquitanus and is part of the Scinax funereus species group. Scinax wekemo sp. nov. is characterized by its yellow, beige, or dark brown dorsum with scattered dark brown spots and a characteristic golden iris. The new species differs from Scinax chiquitanus in texture of the dorsum: shagreen in Scinax wekemo sp. nov. vs. smooth in S. chiquitanus and by the presence of spots on the dorsum (absent in S. chiquitanus).